2017
DOI: 10.3390/ma10121424
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Analyses of Surface Failure Mechanism of Single-Crystal Silicon during Micro-Milling Process

Abstract: This article presents an experimental investigation on ductile-mode micro-milling of monocrystalline silicon using polycrystalline diamond (PCD) end mills. Experimental results indicate that the irregular fluctuation of cutting force always induces machined surface failure, even in ductile mode. The internal mechanism has not been investigated so far. The multiscale discrete dislocation plasticity framework was used to predict the dislocation structure and strain evolution under the discontinuous cutting proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…It was concluded that these parameters had a strong influence on the surface roughness of the micromachine surface. Jinxuan Bai et al [77] focused on the influencing parameters during the ductile mode micromachining in which it was concluded that vibration thrust force causes a brittle fracture and a smooth ductile cutting is achieved by smooth thrust force. Ugur Koklu and Gültekin Basmaci [78] focused on the effect of different tool path strategies with different cooling conditions on cutting force during micromilling.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that these parameters had a strong influence on the surface roughness of the micromachine surface. Jinxuan Bai et al [77] focused on the influencing parameters during the ductile mode micromachining in which it was concluded that vibration thrust force causes a brittle fracture and a smooth ductile cutting is achieved by smooth thrust force. Ugur Koklu and Gültekin Basmaci [78] focused on the effect of different tool path strategies with different cooling conditions on cutting force during micromilling.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, if processing titanium alloy Ti-6Al-4V with large diameter tools, the feed force would be primary and the tool failure is mainly caused the wear in the rake face of cutter. In particular, varying rake angle played a critical part in the formation of chips and influenced the shape-structure and amplitude of thrust force, which has been proved closely relation with finished surface performance by Bai et al [20]. In Fig.…”
Section: Wear Mechanism Of Machining Toolmentioning
confidence: 83%
“…With the development of ultra-hard materials, different kinds of ultra-hard cutting tools such as diamond coated tools, polycrystalline diamond (PCD) tools, and cubic boron nitride (CBN) tools have been used. This makes it possible that materials with high hardness or brittleness, such as engineering ceramics [24,25], tungsten carbide [26,27], silicon [28] and pure tungsten [29] etc., can be directly machined in ductile mode by hard milling. Unlike pure cutting, in which the relative tool sharpness, known as RTS (the ratio of the uncut chip thickness to the cutting edge radius) should be ≥ 10.…”
Section: Introductionmentioning
confidence: 99%